Nusselt Number Correlation for Vertical Tubes with Inverted Triangular Fins under Natural Convection - Byeong Dong Kang (Energies, 2017)
Vertical tubes with inverted triangular fins under natural convection are investigated experimentally. The thermal resistances of tubes with inverted triangular fins are measured for various fin numbers, fin heights, and heat inputs. A Nusselt number correlation that best predicts the measured thermal resistances is proposed. The proposed correlation is applicable to the following conditions: Rayleigh numbers of 1000–125,000, fin height to fin length ratios of 0.2–0.6, and fin numbers of 9–72. Finally, a contour map of the thermal resistances calculated from the proposed correlation for various fin thicknesses and fin numbers is presented. The contour map shows that there exist optimal values of the fin thickness and fin number at which the thermal resistance of the inverted-triangular-finned tube is minimized. Therefore, the proposed correlation enables a search for the optimal dimensions and has potential to be used in the designing of inverted-triangular-finned tubes of various cooling devices.